How Are Students' Creative Thinking Skills Through Microbial Growth Rate Worksheet on Nata De Whey Kefir? - Mas'ud, Asrianty; Kurniati, Tuti; Jaelani, Yusuf (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2024)
Worksheets can be used as a solution to the success of the practicum process. This study aimed to analyze students' creative thinking skills through worksheets of microbial growth rates on nata de whey kefir. The method used in this research was a Pre-Experimental Design with a one-group pretest-posttest design. The population of this research was the sixth-semester Biology Education Study Program students. The research sample consisted of a class of 21 students selected using a purposive sampling technique. The research instrument consisted of description questions containing indicators of creative thinking. The results of the research data analysis obtained an average N-gain for each indicator of creative thinking skills of 0.461, which was included in the